Mortality incidence for SARS-COV-2 non-survivor infected in Colombia: A potential vaccination priority guide based on Comorbidities (2021)
The SARS-CoV-2 vaccination plan development in Colombia, set to begin in February 2021, included a comprehensive assessment of the spread to set population priorities in rank-ordered phases. In Phase 3 of the plan, populations between 16 and 59 years with a set of specific comorbidities will be vaccinated. Our study aims to evaluate the comorbidities incidence in the survival probability to assess the population at most risk if infected and assist in the assignation on this phase. In this study, multivariate Cox regression and Kaplan-Meier curves were performed to determine risk predictors of mortality for 610 reports of up to 15-day decay non-survivor SARS-CoV-2 infected in Colombia. After implementation, higher hazard ratios were associated with diabetes. Kaplan-Meier curves indicate that patients with diabetes that have an older age and hypertension are at a higher risk of earlier death.